Effectiveness of structured Teaching programme on Knowledge regarding prevention of upper respiratory tract infection among parents of children under age of 14 years who are undergoing chemotherapy - Jena, Mrs Sanghamitra (International Journal of Scientific Research and Management (IJSRM), 2017)
Aim to evaluate the effectiveness of structure teaching programme on knowledge regarding prevention of Upper respiratory tract infection among parents of children under age of 14 years who are undergoing chemotherapy. The study was conducted in Basavatarakam Indo-American cancer hospital and research centre, Hyderabad, Telangana, India. The researcher selected 30 parents who fulfilled the inclusion criteria were selected by using simple convenient technique. Data was collected regarding demographic variable and knowledge of prevention of upper respiratory tract infection. The researcher assessed knowledge level of knowledge by using structure questionnaire and followed by structure teaching programme was conducted by one-one method and post-test conducted after 7 days. The analysis finding indicates clearly that percentage distribution of pre-test knowledge scores of parents regarding prevention of upper respiratory tract infection was 44.66% had below average knowledge and 53.34% had average knowledge. Frequency and percentage distribution of post-test knowledge scores of parents regarding prevention of upper respiratory tract infection. In 96.6% had above average knowledge and 3.4% had average knowledge. The effectiveness of programme showed high level of significance at p